2021
DOI: 10.1038/s41598-020-80039-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the immediate behavioral response to partial social exclusion

Abstract: Social rejection and exclusion (ostracism) represent main stressors in daily life and even threaten mental and physical health. Abundant data from subjective measures in social exclusion paradigms are available, but the dynamic behavioral response is largely unexplored. Here, we applied modified variants of the Cyberball paradigm in two consecutive experiments to investigate the adaptive behavioral and emotional reactions to partial social exclusion. In experiment 1, 68 healthy participants (females, mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…An early reference to the need to ensure an individual’s right to education is noted in the United Nations General Assembly ( 1966 ), while more recently, it was stressed that inclusion is a part of the foundation for quality education (Ainscow et al, 2019 ). However, despite several attempts over the years to proceed with an inclusive education model, the majority of these attempts prioritize the location of the student’s instruction rather than the quality of the instruction (Dewald-Kaufmann et al, 2021 ), while the political will, required to succeed in offering inclusive education programs, makes their implementation difficult in practice (Peters, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…An early reference to the need to ensure an individual’s right to education is noted in the United Nations General Assembly ( 1966 ), while more recently, it was stressed that inclusion is a part of the foundation for quality education (Ainscow et al, 2019 ). However, despite several attempts over the years to proceed with an inclusive education model, the majority of these attempts prioritize the location of the student’s instruction rather than the quality of the instruction (Dewald-Kaufmann et al, 2021 ), while the political will, required to succeed in offering inclusive education programs, makes their implementation difficult in practice (Peters, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dewall et al (2007) demonstrated that socially ostracized individuals were more interested in connecting with new friends and working with others, and viewed new others as nicer, friendlier, and more desirable, thereby supporting the idea that relatedness frustration aroused more desire to affiliate and reconnect with others. Dewald-Kaufmann et al (2021) found that excluded participants in a cyberball game immediately passed more balls to the excluder.…”
Section: Coping Strategies Of Need Thwartingmentioning
confidence: 99%
“…Thus, we posited that there are likely observable, emergent cooperative behavioral effects within humans as one's group size increases or decreases, even over typical 1 hr task session timelines. Such group size-mediated behavioral changes have not been rigorously explored in economic laboratory settings, with acute behavioral responses to social rejections and new partnerships over short time-scales (minutes to an hour) being especially understudied (19). However, fully probing group size-mediated effects requires tuning group size dynamically across a given experimental paradigm with a withinsubject design.…”
Section: Main Textmentioning
confidence: 99%